PENGARUH INTENSITAS MODAL, INTENSITAS PERSEDIAAN, KOMISARIS INDEPENDEN DAN KEPEMILIKAN MANAJERIAL TERHADAP ETR - Muhammad Syamsuddin; Trisni Suryarini (Faculty of Economic and Business Universitas STIKUBANK, 2019)
This study aims to analyze the effect of capital intensity, inventory intensity, independent board of commissioners and managerial ownership on the effective tax rate. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. The sample selection uses the purposive sampling method. The results of the sample selection obtained a final sample of 75 companies with an analysis unit of 225. The data analysis of this study used descriptive statistical analysis and Structural Analysis Modeling (SEM) with AMOS 22 software. The results showed that inventory intensity had a significant positive effect on ETR, while for intensity capital, independent board of commissioners and managerial ownership, have no significant effect on ETR. The conclusion of this study is that the size of ETR in manufacturing companies is influenced by inventory intensity. Whereas capital intensity, independent board of commissioners and managerial ownership in manufacturing companies cannot influence the size of the ETR value. Keywords: ETR; capital intensity; inventory intensity; managerial ownership.